Performance Comparison of Typha angustifolia L. and Cyperus alternifolius L. in Landfill Leachate Treatment from Km32 Landfill, Vientiane Capital - Mangnomek, Vienglasy; Lobriayao, Bounphak; Pongmala, Khemngeun; Thibphavong, Monemany; Thammachack, Souliyo; Phonepaseuth, Phongphayboun (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Landfilling is is a common practical method used for waste management in developing countries. The leakage of landfill leachate containing a high amount of Chemical Oxygen Demand (COD) is a main environmental problem during the rainy season. Previous research work has utilized the coagulation-flocculation process to treat this leachate. Although many parameters after treatment could meet the standard, the remaining COD in treated leachate is still high. Thus, this study investigated the ability of two plants species Vis. Typha angustifolia L. and Cyperus alternifolius L. in the subsurface flow of constructed wetlands (SFCW). Three sets of SFCW (45 cm × 30 cm × 25 cm) include unplanted soil (control) were compared. Temperature, pH, Conductivity, DO, COD, NO3-N and SO42- were measured in a 7-day interval until 28 days of the experiment. Both plant species not only reduce pH and conductivity to meet the wastewater discharge standard but also increase DO in treated water. NO3-N was completely removed after 14 days in planted soil. Typha angustifolia L showed the highest removal COD rate with 80.2%, and Cyperus alternifolius L showed the best result with 53.6 % in SO42- removal. In conclusion, these two plant species could utilize as phytoremediation in the landfill site to treat leachate before releasing to the environment.